2022
DOI: 10.5603/gp.a2021.0230
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Cystatin C, Hs-CRP, Neutrophil-Lymphocyte Ratio and Platelet-Lymphocyte Ratio with isolated oligohydramnios

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Ginekologia Polska" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…In agreement with our PLR findings, Erten O et al reported significantly higher cystatin C, hs-CRP, and PLR values in the third trimester in an oligohydramnios group compared to a control group. However, again similarly to the present research, that study found no significant difference in NLR values between the two groups [7]. Smiliary to present study, another study comparing high-risk pregnant women and the normal population in the third trimester also reported no association between NLR values and adverse obstetric outcomes [18].…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In agreement with our PLR findings, Erten O et al reported significantly higher cystatin C, hs-CRP, and PLR values in the third trimester in an oligohydramnios group compared to a control group. However, again similarly to the present research, that study found no significant difference in NLR values between the two groups [7]. Smiliary to present study, another study comparing high-risk pregnant women and the normal population in the third trimester also reported no association between NLR values and adverse obstetric outcomes [18].…”
Section: Discussionsupporting
confidence: 86%
“…[12]. All these inflammatory processes suggest that an inflammatory process plays a role in the pathogenesis of IO [7].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations